Electrical properties of cr/crn nano-multilayers produced by the unbalanced magnetron sputtering technique (2011)
Chromium nitride (CrN) films have been applied to several steels as protective coatings against wear and corrosion due to their excellent mechanical properties and corrosion resistance, and in the electronic field these films are commonly used due to their low electrical resistivity. However, it has been found that multilayers combining metal/ceramic films could enhance mechanical and electrical properties compared with their monolayer counterparts, due to the higher amount and interaction between interfaces. In this work, Cr/CrN nano-multilayers have been produced through the unbalanced magnetron sputtering technique with three different degrees of unbalance, in order to study the influence of this parameter on electrical properties. Cr/CrN multilayers with approximately 1 μm of total thickness and a bilayer period (Λ) of 200 nm, 100 nm, and 20 nm were produced at room temperature on H13 steel and silicon (100); and their microstructure and electrical properties as a function of the magnetic field were evaluated. The phase formation was characterized through x-ray diffraction, and results presented (111) and (200) preferred orientations for all the multilayers. Cross section images were obtained through scanning electron microscopy and a multilayer structure can be clearly seen.